How much do governance and managerial behavior matter in investment decisions? Evidence from failed thrift auctions - Howell, Jann C.; Stover, Roger D. (Journal of Corporate Finance, 2002)
Corporate governance and managerial behavior, both in terms of entrenchment and financial leverage, have been individually shown to directly affect firm performance and to indirectly affect it through influence on other determinants of performance. Employing an empirical model that captures documented interactions among the explanatory variables, we examine the importance of these integrated factors in an investment decision by focusing on the determinants of bank bidding activity for failed thrift institutions. While the endogenous relationships based on previous research appear tractable, their overall addition to the explanatory power of the bidding model based on traditional auction variables is very limited. These results suggest questions that should be further examined regarding how much managerial variables as defined by previous studies actually affect firm investment decisions once their endogeneity and unique linkages are formally recognized.